Distribution and availability of rare earth elements and trace elements in the estuarine waters of the Ría of Huelva (SW Spain). (December 2020) - Cánovas, Carlos Ruiz; Basallote, Maria Dolores; Macías, Francisco
Abstract: Metal pollution in estuaries represents a serious environmental challenge, especially in areas affected by industrial and mining activities. This study investigates the metal partitioning and availability of rare earth elements (REE), Y and other trace metals (Ag, Tl, U and Cs) in the Ria of Huelva estuary (SW Spain), strongly affected by mining and industrial activities. A 30 h monitoring campaign was performed collecting periodic water samples and deploying diffusive gradient in thin films (DGTs) devices to determine the main factors controlling metal availability. The dissolved concentrations of U (3118–3952 ng/L) and Cs (284–392 ng/L) were in the same order of magnitude than those reported in other estuaries and coastal waters worldwide, however, REE (26–380 ng/L), Y (15–109 ng/L), Ag (14–307 ng/L) and Tl (29–631 ng/L) concentrations exceeded these values for the same salinities. Unlike most metals (i.e. Ag, Tl, U, Cs), which were mainly found in the dissolved form (87–100% of total), REE and Y were found in the particulate phase (22–36% of total). Metal lability was mainly related to the concentration in the water column following this order: U>REE>Y>Ag>Tl. A similar binding mechanism was observed for Tl and Cd, due to its chemical affinity. This relationship between chemical properties and absorption by DGT-resin was also observed for REE (and Y), Rb and Sr, which may cause bioaccumulation upon persistent exposure, considering the ability of these metals to cross the biological membranes. The lability of metals predicted by geochemical codes did not coincide with absorption of labile metals by DGTs due probably to the instability of complexes in contact with the DGT membranes, the inability of metals to form thermodynamically stable complexes or the absorption of colloids. From this work it can be concluded that DGT passive sampling should complement traditional sampling to monitor metal availability in aquatic environments. Graphical abstract: Image 1 Highlights: Unless the rest of metals, REE and Y were mainly found in the particulate phase. Higher concentration of REE, Y, Ag and Tl than other estuaries worldwide was found. Metal retention by DGT was related to water concentration rather than to lability. The bioavailability of metals in the estuary follows this order: U>REE>Y>Ag>Tl. REE, Y and U may cross biological membranes and bioaccumulate. Abstract : Capsule: Metal retention (i.e. REE, Y, Ag, Tl, U, Cs) in a strongly polluted estuary by Diffusive Gradient in Thin Films (DGT) was related to water concentration rather than lability.